2004
DOI: 10.1021/es049590h
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Depth Attenuation of Biogenic Phosphorus Compounds Measured by 31P NMR

Abstract: Being a major cause of eutrophication and subsequent loss of water quality, the turnover of phosphorus (P) in lake sediments is in need of deeper understanding. A major part of the flux of P to eutrophic lake sediments is organically bound or of biogenic origin. This P is incorporated in a poorly described mixture of autochthonous and allochthonous sediment and forms the primary storage of P available for recycling to the water column, thus regulating lake trophic status. To identify and quantify biogenic sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(177 citation statements)
references
References 32 publications
10
161
0
2
Order By: Relevance
“…OP in the sediment may be more stable than ortho-P. The half-lives of mono-P, diesters-P, and pyro-P are 23 y, 21 y, and 13 y, respectively in Lake Erken in Sweden (Ahlgren et al, 2005); and the half-lives of various OP forms, namely mono-P, lipid-P, DNA-P, and pyro-P, are 27 y, 14 y, 12 y, and 3 y, respectively in Taihu Lake in China (Ding et al, 2013). The proportion of mono-P was higher in the Liao River and Luan River, and lower in the Yongdingxin River, and it indicated that the phosphorus composition in the Liao River were more stable than in the Yongdingxin River and the Ziya River.…”
Section: P Nmr Spectroscopy and P Fractionationmentioning
confidence: 99%
“…OP in the sediment may be more stable than ortho-P. The half-lives of mono-P, diesters-P, and pyro-P are 23 y, 21 y, and 13 y, respectively in Lake Erken in Sweden (Ahlgren et al, 2005); and the half-lives of various OP forms, namely mono-P, lipid-P, DNA-P, and pyro-P, are 27 y, 14 y, 12 y, and 3 y, respectively in Taihu Lake in China (Ding et al, 2013). The proportion of mono-P was higher in the Liao River and Luan River, and lower in the Yongdingxin River, and it indicated that the phosphorus composition in the Liao River were more stable than in the Yongdingxin River and the Ziya River.…”
Section: P Nmr Spectroscopy and P Fractionationmentioning
confidence: 99%
“…Conditions may be hypoxic at the sediment-water interface, so mono-P in lake sediments may be a key source of phosphate during algal bloom periods. DNA-P and lipid-P were the main components of diester-P, which represents labile P in the sediments and has a half-life of 21 years (Cade-Menun 2005; Ahlgren et al 2005). The significant positive relationship between pyro-P, mono-P, and diester-P indicates that pyro-P might be released from mono-P and diester-P under specific physicochemical conditions.…”
Section: Phosphorus Forms Identified By 31 P-nmrmentioning
confidence: 99%
“…Biogenic-P in the sediment may be more stable than ortho-P. The half-lives of mono-P, diester-P, and pyro-P are 23, 21, and 13 years, respectively in Lake Erken in Sweden (Ahlgren et al 2005); and the half-lives of various biogenic-P forms, namely mono-P, lipid-P, DNA-P, and pyro-P, are 27, 14, 12, and 3 years, respectively, in Taihu Lake in China (Ding et al 2013). From Fig.…”
Section: Phosphorus and Lake Trophic Statusmentioning
confidence: 99%
“…Recent studies have determined the chemical nature of sediment organic P by alkaline extraction and solution 31 P nuclear magnetic resonance (NMR) spectroscopy, which classifies organic P into a series of compounds and functional groups, including phosphomonoesters, phosphodiesters (e.g., DNA, lipids), and phosphonates (e.g., Carman et al 2002;Ahlgren et al 2005;Reitzel et al 2007;Zhu et al 2013). The technique also identifies inorganic phosphates, including orthophosphate, pyrophosphate, and polyphosphate (e.g., Hupfer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the relative importance of the various P forms in sediments will depend on sediment composition, sedimentation rate, diagenesis, and physicochemical conditions (Lopez and Morgui 1993;Gonsiorczyk et al 1998). Of significance is the fact that differences in the abundance of P compounds with depth in lake sediments can provide information on mineralization rates and the contribution of the various compounds to the internal P load (Ahlgren et al 2005;Reitzel et al 2007).…”
Section: Introductionmentioning
confidence: 99%